2019 8th International Conference on Affective Computing and Intelligent Interaction (ACII) 2019
DOI: 10.1109/acii.2019.8925531
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Music to Slow Breathing and Invite Relaxed Physiology

Abstract: We engineered an interactive music system that influences a user's breathing rate to induce a relaxation response. This system generates ambient music containing periodic shifts in loudness that are determined by the user's own breathing patterns. We evaluated the efficacy of this music intervention for participants who were engaged in an attention-demanding task, and thus explicitly not focusing on their breathing or on listening to the music. We measured breathing patterns in addition to multiple peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Focusing on respiration, Harris et al ( 2014 ) modified music by adding white noise that varied according to participants' BR. Leslie et al ( 2019 ) also tested various music modifications depending on the respiratory signal. Sato and Moriya ( 2019 ) used music by controlling the synchronicity with acoustical timing (phrases, pitch change).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on respiration, Harris et al ( 2014 ) modified music by adding white noise that varied according to participants' BR. Leslie et al ( 2019 ) also tested various music modifications depending on the respiratory signal. Sato and Moriya ( 2019 ) used music by controlling the synchronicity with acoustical timing (phrases, pitch change).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study have shown some promises of adaptive breathing guidance. A recently similar study (Leslie et al, 2019) exploring personalized musical breathing guidance has also shown that adaptive guidance could be more effective in slowing down breathing rates and leading to a more calm state. The adaptive guidance enables the flexibility for the system to fit different individuals.…”
Section: Designing Adaptive Guidance To Prevent Fatigue and Enhance Cmentioning
confidence: 92%
“…Most single-modal breathing guidance relies on visual displays, which could take a variety of forms, such as an accurate guiding wave (Park et al, 2009), an evocative metaphorical visualization (Yu et al, 2017), a playful animation or game (Shih et al, 2019;Sonne & Jensen, 2016), or an immersive light environment . Auditory breathing guidance usually employs a simple audio tone (Clark & Hirschman, 1990;Gavish, 2010) and nature sounds (Ettehadi et al, 2020) or uses musical elements (Leslie et al, 2019;. Multi-modal interfaces are usually used for adding extra information to the guidance or enhancing immersive experiences in training.…”
Section: Breathing Guidance Modality and Platformmentioning
confidence: 99%
“…In the corresponding study, music was composed in real-time according to the user's breathing patterns while they were focused on a reaction-time task, without knowledge about how the music was being generated or its potential purpose. Multiple physiological arousal indicators (breathing rate, electrodermal activity (EDA), heart rate, and slow cortical potentials measured in electrocardiographic signals) consistently showed a shift towards a calmer state [22].…”
Section: Related Workmentioning
confidence: 98%